Arcobacter cryaerophilus Isolated From New Zealand Mussels Harbor a Putative Virulence Plasmid - On, Stephen L. W.; Althaus, Damien; Miller, William G.; Lizamore, Darrell; Wong, Samuel G. L.; Mathai, Anso J.; Chelikani, Venkata; Carter, Glen P. (Frontiers in Microbiology, 2019)
A wide range of Arcobacter species have been described from shellfish in various countries but their presence has not been investigated in Australasia, in which shellfish are a popular delicacy. Since several arcobacters are considered to be emerging pathogens, we undertook a small study to evaluate their presence in several different shellfish, including greenshell mussels, oysters and abalone (paua) in New Zealand. Arcobacter cryaerophilus, a species associated with human gastroenteritis, was the only species isolated, from greenshell mussels. Whole-genome sequencing revealed a range of genomic traits in these strains that were known or associated virulence factors. Furthermore, we describe the first putative virulence plasmid in Arcobacter, containing lytic, immunoavoidance, adhesion, antibiotic resistance and gene transfer traits, among others. Complete genome sequence determination using a combination of long- and short-read genome sequencing strategies, was needed to identify the plasmid, clearly identifying its benefits. The potential for plasmids to disseminate virulence traits among Arcobacter and other species warrants further consideration by researchers interested in the risks to public health from these organisms.